Effectiveness of acupuncture and moxibustion combined with rehabilitation training for post-stroke shoulder-hand syndrome: a systematic review and meta-analysis - Huawei Gao; Zhihong Li; Wei Chen; Fangfang Shen; Yan Lu (Frontiers in Neurology)
BackgroundPost-stroke shoulder-hand syndrome (SHS) significantly impacts patients' quality of life and functional recovery. While both acupuncture and rehabilitation training have shown promise individually, their combined effect needs systematic evaluation.MethodsA comprehensive search was conducted across seven databases (PubMed, Embase, Cochrane Library, Web of Science, Sinomed, CNKI, and Wanfang) for randomized controlled trials comparing combined acupuncture-moxibustion-rehabilitation therapy vs. rehabilitation alone. The primary outcomes included Fugl-Meyer Assessment (FMA) scale, visual analog scale (VAS), and Barthel Index (BI) scores. Risk of bias was assessed using the Cochrane tool.ResultsTwenty-seven randomized controlled trials involving 2,175 participants were included. Meta-analysis showed significant improvements in the combination therapy group compared to rehabilitation alone: VAS score (SMD = 1.62, 95% CI: 1.19–2.06), FMA scale (SMD = 1.78, 95% CI: 1.41–2.15), and BI/MBI scores (SMD = 1.01, 95% CI: 0.48–1.54). The combination therapy also showed superior effects on swelling reduction (SMD = −1.75, 95% CI: −2.08, −1.42) and total response rate (RR = 1.21, 95% CI: 1.01–1.44). Most studies demonstrated low to moderate risk of bias.ConclusionThe combination of acupuncture and moxibustion with rehabilitation training appears to be more effective than rehabilitation alone for post-stroke SHS, improving motor function, pain relief, and activities of daily living. However, high heterogeneity warrants careful interpretation and further high-quality studies.